PENINGKATAN KECERDASAN EMOSIONAL MELALUI PEMBELAJARAN DI PESANTREN - Nasron Hakim; Yusuf Arisandi (Research Department (Lemlit) Islamic Institute of Darullughah Wadda’wah Bangil, Pasuruan, 2019)
Abstract One of the means of education in Indonesia and which is the mission of Islam both traditional and modern is the pesantren, an Islamic boarding school that presses its students (students who study at the pesantren are called santri) to behave politely and have good morals which become a reference for daily life, in which there the learning process of understanding and understanding Islamic teachings in depth. On the other hand, Islamic boarding schools are a vehicle to seek knowledge by students and become a community to deepen Islamic religious knowledge, and also contain the meaning of Indonesian authenticity, pesantren began to be known in the archipelago in the 13-17 century and was introduced in Java in the 15-16 century. Key Word : Emotional Intelligence, Learning, Islamic Boarding School